Proglacial lakes and the retreat pattern of the southwest Laurentide Ice Sheet across Alberta, Canada. (1st December 2019) - Utting, Daniel J.; Atkinson, Nigel
Abstract: The extent of proglacial lakes following the initial separation of the southwest Laurentide Ice Sheet from the Cordilleran Ice Sheet and its eastward retreat from the Canadian Rocky Mountains has been reconstructed across regions of Alberta at a range of scales. However, to date, no studies have integrated all available geological information to produce a province-wide deglacial reconstruction that considers the evolution of proglacial lakes as components of the ice-marginal system. In this paper, we utilize a geologically constrained shoreline projection method with a high resolution digital elevation model to reconstruct the evolution of the ice-marginal system along the southwest LIS during the last deglaciation. This method provides new details on the configuration, volume, drainage history and routing of ∼240 proglacial lakes as they migrated across Alberta and establishes a succession of paleogeographic reconstructions that can place geological evidence of regional and local ice-flow reorganizations into a spatiotemporal context. These reconstructions demonstrate that although the evolution of proglacial lakes was largely driven by the topography of the emerging landscape and the configuration of the ice margin, positive feedbacks in the ice-marginal system, particularly where margins transitioned from terrestrial to subaqueous settings played a major role in deglacial ice dynamics. Narrow, ribbon-shaped lakes that paralleled the ice margin induced relatively minor changes in style and rate of deglaciation, whereas the evolution of progressively larger, longer-lived lakes extending obliquely to the ice margin promoted surging and subsequent rapid retreat. Highlights: The retreating Laurentide Ice sheet dammed proglacial lakes over much of the Alberta area. By using an outlet projection method we reconstruct proglacial lakes over the region. We reconstruct the pattern of deglaciation from the relative sequence of proglacial lakes. In the south relatively small proglacial lakes drained through spillways that formed along the lobate ice sheet margin. In the north, larger proglacial lakes developed, promoting surging and subsequently rapid retreat of the ice sheet.